Twitch Advertising and Purchase Intention: The Impact of In-Stream Ads on Viewer Behavior - Brauer, Claudia; Eckert , Judith; Zehrer, Anita (Tecno Scientifica Publishing, 2026)
Twitch, a leading livestreaming platform in the D-A-CH region, combined real-time content with a highly interactive community, offering unique opportunities for digital marketing. Research on advertising effectiveness at the individual viewer level, however, remained limited. This study investigated how in-stream video and display ads influenced Twitch viewers’ purchase intentions and explored the role of ad-related and content-related factors. A survey of 204 Twitch viewers, recruited via Twitch and Reddit, assessed awareness, attitudes, and perceived effects of video and display ads, along with factors such as thematic congruence, entertainment, informativeness, and personalization. Video ads were more effective than display ads in increasing purchase intentions but were perceived as more intrusive. Across formats, thematic alignment with livestream content and content qualities such as entertainment value, informativeness, and personalization significantly enhanced ad effectiveness. The findings highlighted that both ad format and content-related factors were critical for the effectiveness of Twitch advertising. The study advanced theoretical understanding of livestream advertising by emphasizing the interplay between ad characteristics and content context and provided practical guidance for marketers to design engaging, congruent, and less intrusive campaigns.